THE ROLE OF FAMILY DYNAMICS IN VIKRAM SETH'S A SUITABLE BOY - Singh, K D; Manglia, Javed Khan; Choudhary, Seema (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper delves into the complex role of family dynamics in Vikram Seth's A Suitable Boy, a novel set against the backdrop of post-independence India. By examining the interactions and relationships within the Mehra, Kapoor, Khan, and Chatterji families, the study highlights how Seth portrays the multifaceted nature of family life as a reflection of broader societal changes. The novel intricately intertwines personal and political narratives, using family as a lens through which the reader can explore themes of tradition versus modernity, individual autonomy versus societal expectation, and the clash between generational values. Through the characters' personal dilemmas and family obligations, Seth reflects the socio-political tensions of a nation in transition. The study investigates how the pursuit of a 'suitable boy' for Lata Mehra symbolizes the broader quest for identity, stability, and continuity in a rapidly changing society. By focusing on the intricacies of familial relationships and the social expectations they embody, this paper aims to illustrate how Seth's narrative not only captures the essence of Indian family life but also serves as a microcosm of the country's evolving cultural and ideological landscape. This analysis offers insights into the significant role family dynamics play in shaping individual and collective identities within the novel.